PERAN SOCIAL SUPPORT TERHADAP RELATIONSHIP QUALITY DAN SOCIAL COMMERCE INTENTION - Widarto Rachbini (Universitas Mercu Buana, 2017)
Abstract: In the era of social commerce, individuals share their knowledge,experience, and information about products and services with people in theirneighborhood or close friends. Formed on the basis of social support theory,relationship quality, and social media concepts, this study proposes a model thataims to investigate or analyze more deeply about the role of social factors thatinfluence relationship quality with its three dimensions (commitment, trust andsatisfaction), as well as social commerce intention. Surveys were conducted usingonline-survey platforms and questionnaires distributed on which are the mostpopular social networking sites in Indonesia (APJII, 2016), and the PLS-SEMmethod was used to prove empirically the proposed model. The results of thisstudy related to social factors that give a significant influence on relationshipquality and social commerce intention. This study highlights the changingbehavior of consumers in the era of social commerce. It also contributespositively to the development of theory in the context of social commerce.Practically, the results of this study indicate that technology changes in the ecommerceis a new opportunity and challenge for practitioners to be able toadjust and take advantage of these opportunities.Keywords: social commerce, social support, relationship quality, social media